2012
DOI: 10.2478/s13545-012-0015-1
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Ipomoea aquatica and Utricularia reflexa with phytoplankton densities in a small water body in northern Nigeria

Abstract: The interactions of Ipomoea aquatica and Utricularia reflexa with phytoplankton densities were studied in a small water body in Zaria, Nigeria from June to November 2007. The negative effects of both macrophytes on 10 out of 15 phytoplankton taxa, including Staurastrum sp., Netrium sp., Ulothrix sp., Marssionella sp. and Closterium sp. were differentiated from other environmental effects. U. reflexa, on the other hand, showed positive associations with species like Actinocyclus sp., Palmellopsis sp., Spirotaen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The differences in zooplankton distributions and assemblage in this study may be due to sampling space, time and the dynamic nature of aquatic systems (Iloba 2019). Changes in zooplankton populations in Dangana lake could be attributed to different species having their nutritional requirement of different temperature, pH, DO, BOD5 and nutrients (Chia et al 2012). High nutrient level, high concentration of nitrate, and phosphate favor the growth of Baccillariophyta which forms the major diet of zooplankton (Chia et al 2012).…”
Section: Zooplankton Structural Assemblage and Diversitymentioning
confidence: 99%
“…The differences in zooplankton distributions and assemblage in this study may be due to sampling space, time and the dynamic nature of aquatic systems (Iloba 2019). Changes in zooplankton populations in Dangana lake could be attributed to different species having their nutritional requirement of different temperature, pH, DO, BOD5 and nutrients (Chia et al 2012). High nutrient level, high concentration of nitrate, and phosphate favor the growth of Baccillariophyta which forms the major diet of zooplankton (Chia et al 2012).…”
Section: Zooplankton Structural Assemblage and Diversitymentioning
confidence: 99%
“…Phytoplankton Assemblage of Dangana Lake Plankton abundance and distribution are affected by seasonal changes of both physical and chemical parameters as well as microplant life in aquatic environments [31]. Changes in plankton population in the lake could be distributed to various species having t different nourishment in temperature, pH, Do, BODs and nutrients [32]. High nutrient levels such as nitrate and phosphate enhance the growth of Baccillariophyta which forms the major diet of zooplankton [32].…”
Section: Spatial and Temporal Variation Inmentioning
confidence: 99%
“…Changes in plankton population in the lake could be distributed to various species having t different nourishment in temperature, pH, Do, BODs and nutrients [32]. High nutrient levels such as nitrate and phosphate enhance the growth of Baccillariophyta which forms the major diet of zooplankton [32]. In this study a significant abundance of some phytoplankton species were observed this could be attributed to increase in the intensity of solar radiation that can be captured by phytoplankton, hence increased photosynthesis and other metabolic activities which lead to a subsequent increase in population density of planktons [12,33].…”
Section: Spatial and Temporal Variation Inmentioning
confidence: 99%
“…Successional studies show that the occurrence of Cylindrospermopsis blooms is usually accompanied by the presence of chlorophytes of the genera Monoraphidium and Scenedesmus (Bouvy et al 1999(Bouvy et al , 2006Kokociński et al 2010). Furthermore, there is evidence of the alternation between the dominance of green microalgae and cyanobacteria in different aquatic ecosystems (Zalocar de Domitrovic et al 2007;Chia et al 2012). However, the chemical interactions involved in this successional process are still not comprehensively understood.…”
Section: Introductionmentioning
confidence: 99%